Polityka Turcji wobec Bałkanów Zachodnich po 2008 roku - Tadeusz Kopyś (Politeja, 2018)
With the disintegration of Yugoslavia, all the balances in the Balkans were altered and the instability that arose from this process reached a level that threatened international peace. The historical ties between the peoples of Turkey and countries of the region have extended until today. There are Turkish minorities and communities as well as kin communities in the Balkan countries on the one hand; whereas there are citizens of Balkan‑origin in Turkey on the other. Turkey aims to initiate a psychological breakthrough in the Balkans to undo the negative memories of the past. At the regional level, Turkey follows three different sets of policies. The first is to develop bilateral relations to the possible highest extent. The second track is the creation of trilateral mechanisms, such as between Turkey, Serbia, and Bosnia; and Turkey, Croatia, and Bosnia‑Herzegovina. The third track aims to achieve region‑wide cooperation efforts and foster economic interdependence to secure the future of the political relations.